PENGARUH PEMBELAJARAN MICRO TEACHING TERHADAP KETERAMPILAN MENGAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN PANCASILA & KEWARGANEGARAAN DI UNIVERSITAS PGRI WIRANEGARA - Akhmad Afandi; Ayu Maya Damayanti; Alman Farizi; Regita Ajeng Tri Hapsari (STKIP Pesisir Selatan, 2026)
A crucial part of preparing future teachers is microteaching, which aims to build targeted and long-lasting teaching abilities. The purpose of this study is to characterize how microteaching affects the teaching abilities of students enrolled in PGRI Wiranegara University's Pancasila and Citizenship Education Study Program. This study used descriptive-interpretive techniques in a qualitative manner. Observation, interviews, and documentation of students' microteaching techniques were used to collect data. The study's findings show that microteaching has a beneficial effect on students' development of teaching abilities, particularly those pertaining to lesson design, execution, classroom management, and assessment. Additionally, students' professional attitudes such as self-assurance, accountability, discipline, and receptivity to criticism are shaped by microteaching. Microteaching in the framework of civics (PPKn) education aids students in acquiring teaching techniques focused on fostering morals and character. As a result, microteaching strategically contributes to improving students' professional preparedness as future educators. Thus, microteaching becomes an important foundation in producing PPKn teachers who are competent, reflective, adaptive, and ready to face the dynamics of learning in schools.